Multidimensional disparity in inadequate minimum dietary diversity between poor and non-poor children aged 6–23 months in Sub-Saharan Africa: a multivariate decomposition analysis - Endawkie, Abel; Tsega, Yawkal; Asmamaw, Desale B.; Kebede, Natnael; Arefaynie, Mastewal; Mawugatie, Temeselew Woldetsadik (Frontiers in Public Health, 2025)
BackgroundSustainable Development Goal (SDG) 2 aims to “end hunger, achieve food security, and improve nutrition” by 2030. However, the prevalence of inadequate Minimum Dietary Diversity (MDD) is on the rise in Sub-Saharan Africa (SSA). Therefore, this study aimed to assess the disparities between multidimensional poor and non-poor households in terms of inadequate MDD among children aged 6 to 23 months in SSA, using data from the 2018–2023 Demographic and Health Survey (DHS).MethodsThe study utilized data from a nationally representative weighted sample of 352,463 children aged 6 to 23 months, drawn from the latest rounds of the DHS in 18 SSA countries. A decomposition analysis was performed to assess the disparity in inadequate MDD between multidimensionally poor and non-poor Households. This analysis divided the disparity into two components: one related to differences in the levels of determinants (endowments) between the poor and non-poor, and the other concerning variations in the effects of the covariates.ResultsThe overall prevalence of inadequate MDD among children in SSA was 89.05%. This prevalence was highest in Central Africa at 90.55% and lowest in South Africa at 87.8%. The difference in inadequate MDD between multidimensional poor and non-poor children was highest in East Africa at 6.15%, which was statistically significant. Factors such as women’s education, husband’s educational status, the employment status of both parents, household wealth index, place of residence, family size, and the number of children significantly contributed to the disparity in inadequate MDD among children from multidimensional poor and non-poor households in SSA.ConclusionThe study highlights a concerningly high prevalence of inadequate MDD among children in SSA, with significant disparities observed between multidimensionally poor and non-poor households. The largest gap in inadequate MDD between poor and non-poor households was found in East Africa. Key factors contributing to these disparities include women’s education, husband’s educational status, the employment status of both parents, household wealth index, place of residence (urban vs. rural), family size, and the number of children. The findings underscore the urgent need for targeted interventions to address inadequate MDD among young children in SSA. Efforts should focus on reducing poverty, improving maternal education, and enhancing employment opportunities, particularly for women, by promoting equitable economic prospects. Addressing these underlying factors is essential to closing the gap in dietary diversity and improving the nutritional outcomes of children in the region.